2015
DOI: 10.31901/24566322.2015/09.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement in the Process of Implementation of the National School Nutrition Programme in Public Schools

Abstract: Inevitably, life in the twenty-first century globalised world brings people into contact with "others". Through these contacts, the need for interactions demands that these people find different ways of understanding one another to generate knowledge. In order for them to achieve this objective, they need a strong and coherent medium. First additional language education has been developed in South Africa to unravel as well as address challenges posed to competence in intercultural communication, with the empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Seeing parents involved in the education of their children is a good thing because it improves academic performance. Students become more focused on their school work (Kwatubana & Makhalemele, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Seeing parents involved in the education of their children is a good thing because it improves academic performance. Students become more focused on their school work (Kwatubana & Makhalemele, 2015).…”
Section: Resultsmentioning
confidence: 99%
“… 8 Delays may result in non-delivery of food items as were reported by some participants and respondents in the study, and affirmed in Kwatubana and Makhalamele’s South African study. 19 Regular meetings with stakeholders may be critical in finding solutions for late payment of stakeholders. Participants in this study, and as also observed in the study by Kwatubana and Makhalamele make it clear that where service providers were reported to be unreliable, the schools lose confidence in the supplier.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this study, and as also observed in the study by Kwatubana and Makhalamele make it clear that where service providers were reported to be unreliable, the schools lose confidence in the supplier. 19 Effective monitoring and communication may be crucial in ensuring the reliability of stakeholders. Late payment of service providers could also result in delays in serving meals, as was reported by participants and respondents in this study and affirmed in Dei’s South African study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School leaderships need to facilitate parents about their children and to give them opportunities to help the schools in achieving their mission and goal (Sapungan & Sapungan, 2014). Parents' involvement can improves academic performance of their children and it also provides them opportunities to show their potentialities and skills in a better manner and they also become more focused in their study (Kwatubana & Makhalemele, 2015). Lemmer (2007) stated that parents' communication with schools can improve their children's self-esteem, attendance and best social behavior.…”
Section: Research Questionsmentioning
confidence: 99%